1989
DOI: 10.1159/000125183
|View full text |Cite
|
Sign up to set email alerts
|

Central Actions of Adenosine on Pituitary Secretion of Prolactin, Luteinizing Hormone and Thyrotropin

Abstract: Pituitary hormones were measured in plasma in unanesthetized male and female rats prepared with venous and ventricular cannulae following ventricular infusions of adenosine and two adenosine receptor agonists. Adenosine (10, 100, and 200 nmol) injected intraventricularly caused dose-related rises in plasma prolactin (PRL) in males; in females, only the 100- and 200-nmol doses increased PRL. Similar doses of adenosine had little effect on plasma levels of luteinizing hormone (LH) and thyrotropin (TSH) in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The failure of rolipram to increase ir‐LH release suggests that mechanisms other than PDE‐4 inhibition may mediate the increases in LH release produced by denbufylline in vivo. An obvious possibility is blockade of adenosine A 1 receptors, although the apparent failure of an adenosine A 1 receptor agonist to influence serum ir‐LH when injected into the lateral ventricle (Ondo et al , 1989) does not accord with this view; nor does the inability of BRL 61063 to augment the secretion of the gonadotrophin.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of rolipram to increase ir‐LH release suggests that mechanisms other than PDE‐4 inhibition may mediate the increases in LH release produced by denbufylline in vivo. An obvious possibility is blockade of adenosine A 1 receptors, although the apparent failure of an adenosine A 1 receptor agonist to influence serum ir‐LH when injected into the lateral ventricle (Ondo et al , 1989) does not accord with this view; nor does the inability of BRL 61063 to augment the secretion of the gonadotrophin.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine has been reported to inhibit prolactin and growth hormone secretion from clonal pituitary cell lines (Dorflinger & Schonbrunn, 1985;Delahunty et al 1988), and either to stimulate or to inhibit the release of adrenocorticotrophic hormone from cultured an¬ terior pituitary cells (Anand-Srivastava et al 1989). Adenosine and adenosine analogues have also been reported to stimulate prolactin and luteinizing hormone release in vivo (Ondo et al 1989), while little (Ondo et al 1989) or no (Di Renzo et al 1990) effect has been described on the 'in-vivo' secretion of thyroid-stimulating hormone.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have shown that peripheral [67] or central [68] administration of adenosine can stimulate the release of PRL but not LH [68] or TSH [69]. These data, however, gave little insight into the site or mode of action of adenosine in the neuroendocrine system, and could in fact represent non-specific stressful actions.…”
Section: Biological Effects Of Purines In the Pituitary Gland Effectsmentioning
confidence: 99%